Effect of SWD in the management of pelvic inflammatory disease (PID) - Shoma, FK; Mahmood, K; Hossain, MS (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10546 J. Dhaka Med. Coll. 2011; 20(2): 178-182